Comparison of beam theories for characterisation of a NREL wind turbine blade flap-wise vibration. (November 2022) - Algolfat, Amna; Wang, Weizhuo; Albarbar, Alhussein
The harsh weather conditions offshore wind turbine blades are working under have necessitated the need for a more effective approach for detecting their failures. Dynamic characteristics e.g., vibration, carry useful information related to blades structural health. Critical analysis of the blade's free vibration represents one of the fundamental steps for assessing structural dynamics. When a rotating blade deflects, either in the plane of rotation or perpendicular to it, the centrifugal force exerts inertia force along the blade span, which increases the blade's natural frequencies compared with the stationary ones. However, the influence of different blade parameters on the flap-wise vibrations is not very well understood. In this paper, the effects of such parameters on dynamic characteristics of National Renewable Energy Laboratory (NREL) 5-MW wind turbine blades are investigated using different beam theories. The examined models have been used to determine the natural frequencies and mode shapes of the National Renewable Energy Laboratory (NREL) 5-MW wind turbine. Results demonstrate that increasing angular velocity significantly impacts the natural frequencies and mode shapes. The rotary inertia is found to influence the free vibration responses of the studied blades. Moreover, increasing hub radius, pre-cone and pitch angles are found to have less influence on the natural frequencies. Mode shape comparisons were also carried out using MSF (modal scale factor) and MAC (modal assurance criteria). Compared to the other investigated methods, Bernoulli's based algorithms are found to produce less accurate results.